Integrating E-Learning into Arabic Pedagogy: Enhancing Graduate Linguistic Competence in Chennai - Ahamed Zubair (IJAS: International Journal of Arabic Studies, 2025)
This study examines how e-learning develops graduate-level Arabic skills in Chennai’s higher education institutions and explores challenges to its integration. Using a descriptive-analytical approach, it surveys Arabic faculty and reviews pedagogical literature on teaching Arabic in non-Arabic contexts. Findings reveal that despite faculty technical competence; institutional adoption of e-learning remains low. Curricula are not digitally aligned, leaving graduates underprepared for technology-driven Arabic professions. Key barriers include limited funding, adherence to traditional pedagogy, and inadequate training in digital teaching tools. The study recommends modernizing Arabic curricula through e-learning, establishing faculty development programs in digital pedagogy, and forming institutional partnerships to improve technological infrastructure. This research contributes to Arabic education discourse in India and proposes a framework for digital transformation in foreign language instruction.